2020
DOI: 10.1002/jsde.12409
|View full text |Cite
|
Sign up to set email alerts
|

Extraction Separation of Rhamnolipids by n‐Hexane via Forming Reverse Micelles

Abstract: Rhamnolipids (RL) have been regarded to be insoluble in n‐hexane. Unexpectedly, we have noticed that RL could be extracted together with vegetable oil by n‐hexane at analyzing oil content of fermentation broth. This paradoxic phenomenon was assumed to be due to the formation of reverse micelles. As found in this paper, the micelle size as well as conductivity increased due to water solubilization, illustrating the formation of reverse micelles of RL in n‐hexane. In this reverse micellar system, the maximal wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
(43 reference statements)
0
2
1
Order By: Relevance
“…The method of extracting rhamnolipids using n-hexane used in the present study deviates from the previous literature reports by Müller et al and El-Housseiny et al who reported the use of n-hexane to determine the oil content in the fermentation media but not for rhamnolipids extraction from this oil-containing medium [16,17]. On the contrary, a recent report by Zhou et al suggested that rhamnolipids could be extracted from the fermentation broth using n-hexane in the presence of oil due to the formation of reverse micelles [18]. Zhou et al first performed acid precipitation of rhamnolipids produced in an oil-containing fermentation medium followed by its extraction with n-hexane.…”
Section: Rhamnolipids Production Processcontrasting
confidence: 97%
“…The method of extracting rhamnolipids using n-hexane used in the present study deviates from the previous literature reports by Müller et al and El-Housseiny et al who reported the use of n-hexane to determine the oil content in the fermentation media but not for rhamnolipids extraction from this oil-containing medium [16,17]. On the contrary, a recent report by Zhou et al suggested that rhamnolipids could be extracted from the fermentation broth using n-hexane in the presence of oil due to the formation of reverse micelles [18]. Zhou et al first performed acid precipitation of rhamnolipids produced in an oil-containing fermentation medium followed by its extraction with n-hexane.…”
Section: Rhamnolipids Production Processcontrasting
confidence: 97%
“…The BS product obtained from solvent extraction and/or acid precipitation is often described as being completely pure, but this is not the case, since the product usually still contains up to 60% water and a number of other contaminants [55]. Ethyl acetate is the most common extracting solvent that is used either alone or in combination with other solvents, such as methanol and chloroform [76,80,97,[102][103][104][105][106][107]. The use of ethyl acetate and chloroform in the production of environmentally sustainable products is not advisable, since these solvents are toxic and must be used in large amounts for these extraction procedures [98].…”
Section: Downstream Processingmentioning
confidence: 99%
“…The use of ethyl acetate and chloroform in the production of environmentally sustainable products is not advisable, since these solvents are toxic and must be used in large amounts for these extraction procedures [98]. Zhou et al (2020) suggest that these unfavorable solvents could be replaced by n-hexane, a less-harmful solvent [97].…”
Section: Downstream Processingmentioning
confidence: 99%